Scenario Planning Analysis for Startup Business Case Study: Beqyu Restaurant - Merdyka, Miranti Sondang; Sunitiyoso, Yos (The Indonesian Journal of Business Administration, 2014)
Abstract - This study describes the application of the scenario planning analysis at the BeQyu Restaurant which was born because of the promising opportunity for restaurant business in Jakarta city with over nine million people population. As a new player, restaurant BeQyu has some internal and external issues that impact on the sustainability of the company in the future. The technique used in this method is to collect data and information to be analyzed in order to generate predictions as a preparation for decision making process. This method give an overview of early warning, implications and options in each scenario drawn from the analysis of external and internal as recommendation for the company which could be used as a reference in determining and developing company’s business strategy. Keywords: BeQyu Restaurant, scenario planning, strategic decision making, restaurant industry.